2002
DOI: 10.1179/016164102101200564
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve regeneration by bone marrow stromal cells

Abstract: Adult bone marrow contains stem cells that have attracted interest through their possible use for cell therapy in neurological diseases. Bone marrow stromal cells (MSCs) were harvested from donor adult rats, cultured and pre-labeled with bromodeoxyuridine (BrdU) previously to be injected in the distal stump of transected sciatic nerve of the rats. Distal nerve stump of control rats received culture medium solution. MSCs-treated rats exhibit significant improvement on walking track test at days 18 and 33 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
93
0
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 16 publications
8
93
0
9
Order By: Relevance
“…Cuevas et al described the migration and integration of MSCs following the injection into the site of a sciatic nerve repair [14]. Terenghi et al treated MSCs with glial growth factor, a powerful Schwann cell mitogen, to induce them to GFAP and S-100 positive cells and recognized a small population of Schwann cell-like cells within the treated MSCs [67].…”
Section: Induction Of Schwann Cells From Mscsmentioning
confidence: 99%
“…Cuevas et al described the migration and integration of MSCs following the injection into the site of a sciatic nerve repair [14]. Terenghi et al treated MSCs with glial growth factor, a powerful Schwann cell mitogen, to induce them to GFAP and S-100 positive cells and recognized a small population of Schwann cell-like cells within the treated MSCs [67].…”
Section: Induction Of Schwann Cells From Mscsmentioning
confidence: 99%
“…42 Furthermore, the transition from stem cell to Schwann cell has been encountered previously and thus indicates that this could be a vital factor in explaining the beneficial effect. 6,7,39,45 Schwann cells, however, not only myelinate; Höke et al 14 showed that the Schwann cell phenotype can be modulated, for example, into motor or sensory Schwann cells. Also, the stem cells offer a more supporting and productive role, producing neural growth stimulating factors.…”
mentioning
confidence: 99%
“…As demonstrated previously, BMSCs implanted within the conduits can synthesize neurotrophic factors and extracellular matrix elements for peripheral nerve regeneration (2,25). Furthermore it was well documented that BMSCs can differentiate exclusively into SCs in vivo (3,6,25) and in vitro (7,11,12,16,18,23) and promote axonal regeneration if the appropriate microenvironment or cell culture conditions were constituted.…”
mentioning
confidence: 67%
“…BMSCs have pluripotent plasticity to differentiate into different cells including neural cell lineage under convenient conditions (9). Recently, introduction of undifferentiated (2,6,12,20) and transdifferentiated (7,11,(16)(17)(18) BMSCs into nerve conduits represents a popular approach for peripheral nerve regeneration. It has been demonstrated that BMSCs in the surgical repair of peripheral nerves have improved axonal regeneration and functional recovery.…”
Section: Histological and Immunohistological Resultsmentioning
confidence: 99%